Testing the Tropical Trigger Hypothesis of Abrupt Climate Variability - Oughton, Jack W.; Urrego, Dunia H. (Frontiers in Earth Science, 2021)
Dansgaard-Oeschger oscillations (DOs) are abrupt shifts in climate, which are dramatic temperature fluctuations observed in Greenland and recorded globally. These abrupt changes are associated with the slowing and shutting down of the Atlantic Meridional Overturning Circulation (AMOC), but despite their importance the driving forces of DOs are not fully understood. Here we assess the role of the AMOC during DOs, the Northern vs Southern Hemisphere control on AMOC, and the possibility of neotropical moisture as a driver for abrupt climate variability. During DOs, South America has recorded a disparity between the degree of warming, and the change in precipitation at different sites. Based on our current understanding, we propose likely oceanic and continental changes in tropical South America that can help disentangle the triggers of these events. With the margins of error associated with dating sources of palaeo-data, the need for an independent chronology with multiple proxies recorded in the same record, could offer the information needed to understand the driving forces of DOs.